The Effect of E-Performance Usage on Teacher Performance at UPTD SMP Negeri 1 Gunungsitoli Barat - Maria Febrina Zebua; Suka’aro Waruwu; Fatolosa Hulu; Yamolala Zega (LPPM Universitas Ekasakti, 2025)
This study aims to determine the effect of the use of E-Performance on the performance of teachers at UPTD SMP Negeri 1 Gunungsitoli Barat. The research method used is a quantitative approach. The sample in this study consists of 30 respondents. Data collection techniques were conducted through observation and the distribution of questionnaires. Data analysis techniques used instrument tests, classical assumption tests, t-tests, and the coefficient of determination with the SPSS version 31 application. Based on the data analysis, it shows that partially, the variable of E-Performance usage has a positive and significant effect on teacher performance with a significance level of 0.001 < 0.05 and a calculated t value of 8.953 > 1.697. In the coefficient of determination test, the effect of E-Performance usage on teacher performance is obtained at 0.613 or 61.3%, while the remaining 38.7% is caused by other factors not included in this study. The conclusion of this research is that the variable of E-Performance usage, both partially and based on the coefficient of determination results, has an effect on teacher performance, and it is recommended for UPTD SMP Negeri 1 Gunungsitoli Barat.